Вивчення ролі міжклітинних медіаторів у механізмі формування дуоденальної виразки у підлітків = Studying the role of intercellular mediators in the mechanism of formation of duodenal ulcer in adolescents - Pavlov, S. B.; Pavlova, G. B.; Strashok, L. A. (Journal of Education, Health and Sport, 2016)
Pavlov S. B., Pavlova G. B., Strashok L. A. Вивчення ролі міжклітинних медіаторів у механізмі формування дуоденальної виразки у підлітків = Studying the role of intercellular mediators in the mechanism of formation of duodenal ulcer in adolescents Journal of Education, Health and Sport. 2016;6(10):625-636. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.192161 http://ojs.ukw.edu.pl/index.php/johs/article/view/4034 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. Вивчення ролі міжклітинних медіаторів у механізмі формування дуоденальної виразки у підлітків С. Б. Павлов, Г. Б. Павлова, Л. А. Страшок Харківська медична академія післядипломної освіти Резюме Вступ. Актуальним питанням в гастроентерології залишається проблема виразок, що довго не загоюються, коли рубцювання виразкового дефекту слизової оболонки, незважаючи на інтенсивність лікування, сповільнюється. В основі патогенезу ерозивно-виразкових уражень дванадцятипалої кишки лежать порушення стереотипного процесу репаративної регенерації, яка визначається функціональним станом сполучної тканини балансом регуляторних систем на рівні міжклітинних медіаторів. Метою роботи було визначення профілів міжклітинних медіаторів та їх значущості у розвитку порушень загальної схеми регуляції процесів ремоделювання сполучної тканини та ролі у механізмах формування дуоденальної виразки у підлітків. Матеріали і методи. Досліджувану групу склали 70 підлітків (юнаків - 42, дівчат - 28) у віці 15-18 років, які страждають на виразкову хворобу дванадцятипалої кишки. Вивчали вміст цитокінів (IL-1β, IL-4, IL-6, TNF-α ) у сироватці крові методом імуноферментного аналізу. Результати дослідження. Встановлено, що у підлітків з дуоденальною виразкою рівні прозапальних цитокінів IL-1β та IL-6 в фазу загострення захворювання були достовірно вищими за такі в контрольній групі (перевищували норму у 1,4 – 2 рази) і не залежали від статі. Концентрація IL-4 зросла у 5,6 рази. Рівень TNF-α був достовірно знижений, найбільш значно у дівчат (у юнаків в 1,4 рази, у дівчат - в 1,9 рази). У фазу ремісії у дівчат вміст IL-1β, IL-6 та IL-4 нормалізувався. У всіх підлітків з дуоденальною виразкою зберігався дефіцит TNF-α, а у юнаків залишались підвищеними рівні IL-1β та IL-6. Вміст IL-4 у юнаків не тільки не нормалізувався, але навіть підвищувався (до 209±31,5 пкг/л, р<0,05) порівняно з фазою загострення. Аналіз вмісту вивчених цитокінів у підлітків з дуоденальною виразкою залежно від етіопатогенетичних факторів виявив їх найбільшу зміну у пацієнтів з Helicobacter pylori-негативним захворюванням. У юнаків вміст вивчених цитокінів змінювався більш значно при обтяженій за виразковою хворобою спадковості і підвищеній кислотності шлункового соку, а у дівчат - при нормальній кислотності і необтяженій спадковості. Висновки. У підлітків, які страждають на виразкову хворобу дванадцятипалої кишки спостерігається дисбаланс в системі регуляції функціональної системи сполучної тканини на рівні міжклітинних медіаторів який проявився підвищенням рівнів IL-1β, IL-6, IL-4, недостатньою продукцією TNF-α, та відображає наявність патологічної деактивації процесів біосинтезу компонентів позаклітинного матриксу. Виявлені зміни можуть свідчити про порушення загальної схеми регуляції процесів ремоделювання сполучної тканини та зниження резервів адаптації організму. Ключові слова: міжклітинні медіатори, виразкова хвороба, гастроентерологія Studying the role of intercellular mediators in the mechanism of formation of duodenal ulcer in adolescents S. B. Pavlov, G. B. Pavlova, L. A. Strashok Kharkiv Medical Academy of Postgraduate Education Abstract Introduction. Current issues in gastroenterology is the problem of ulcers, long healing when scarring of the ulcer mucosa, despite the intensity of treatment is slowing. The pathogenesis of erosive and ulcerative lesions of the duodenum are violations stereotypical reparative regeneration process, defined functional state of connective tissue balance regulatory systems at intercellular mediators. The aim was to identify profiles intercellular mediators and their significance in the development of common disorders circuit regulation of connective tissue remodeling and role in the mechanisms of formation of duodenal ulcer in adolescents. Materials and methods. Investigated group consisted of 70 teenagers (boys - 42, women - 28) aged 15-18 years, suffering from duodenal ulcer. We studied the contents of cytokines (IL-1β, IL-4, IL-6, TNF-α) in serum by enzyme immunoassay. Research results. Found that in adolescents with duodenal ulcer levels of proinflammatory cytokines IL-1β and IL-6 inthe acute phase of the disease were significantly higher than those in the control group (rate exceeded the 1.4 - 2 times) and does not depend on gender. The concentration of IL-4 increased by 5.6 times. TNF-α level was significantly lowered, most significantly in girls (boys 1.4 times in women - 1.9 times). In the remission phase in girls contents of IL-1β, IL-6 and IL-4 returned to normal. All adolescents with duodenal ulcer persisted deficit TNF-α, while the boys remained elevated levels of IL-1β and IL-6. The content of IL-4 for youths not only normal, but even increased (to 209 ± 31.5 pg / l, p <0.05) compared to the aggravation phase. Content analysis of cytokines studied in adolescents with duodenal ulcer depending on factors etiopathogenetical found their greatest change in patients with Helicobacter pylori-negative disease. In boys studied cytokine content changed more significantly during burdened by heredity ulcer and increased acidity of gastric juice, and the girls - under normal acidity and burdened heredity. Conclusions. Adolescents suffering from duodenal ulcer observed imbalance in the system of regulation of the functional system of connective tissue at intercellular mediators which manifested increased levels of IL-1β, IL-6, IL-4, insufficient production of TNF-α, and reflects a pathological deactivation processes of biosynthesis of extracellular matrix components. Identified changes may indicate a violation of a framework for the regulation of connective tissue remodeling and reduce reserves adaptation. Keywords: intercellular mediators, peptic ulcer disease, gastroenterology